2017
DOI: 10.1088/1361-665x/aa5aae
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light-responsive photorheological fluids: as a new class of smart fluids

Abstract: We present a comprehensive introduction to the photorheological (PR) fluids whose rheological behavior can be changed by ultraviolet (UV) light with a wavelength of 365 nm. When the PR fluid was exposed to UV light, the viscosity of the fluid decreased, while the viscosity recovered to its initial value when UV light was turned off, indicating that the viscosity of these types of fluids can be reversible and tunable by UV light. Contrary to conventional smart fluids, such as electrorheological and magnetorheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In contrast, ER fluids that have the opposite behavior (i.e., those that show decreased shear stress and viscosity under an applied electrical field) are called negative ER fluids [ 74 , 75 , 76 , 77 ]. However, the characteristics of both types of ER fluids can be improved through light lamination; these are called photo-electrorheological (photo ER) fluids [ 78 , 79 ]. Photogenerated carriers are considered to be responsible for changing the electric properties of the positive or negative materials and enhancing their ER phenomena.…”
Section: Electrorheological Fluidsmentioning
confidence: 99%
“…In contrast, ER fluids that have the opposite behavior (i.e., those that show decreased shear stress and viscosity under an applied electrical field) are called negative ER fluids [ 74 , 75 , 76 , 77 ]. However, the characteristics of both types of ER fluids can be improved through light lamination; these are called photo-electrorheological (photo ER) fluids [ 78 , 79 ]. Photogenerated carriers are considered to be responsible for changing the electric properties of the positive or negative materials and enhancing their ER phenomena.…”
Section: Electrorheological Fluidsmentioning
confidence: 99%
“…When the viscosity of UPPG is higher than viscosity of PDMS, ER effect of the suspension is positive. When the viscosity of UPPG is lower than viscosity of PDMS, the ER effect of the suspension is negative [42].…”
Section: Negative Er Effectmentioning
confidence: 99%
“…These fluids have attracted increased attention since Lee et al reported that they can be easily synthesized in the laboratory using commercially available chemicals and ingredients, such as spiropyran, instead of using conventional ingredients, such as trans-ortho-methoxycinnamic acid, alpha-cyclodextrin, and hydroxyethyl cellulose [ 1 , 2 , 3 , 4 ]. PR fluids are characterized by changes in their properties such as color and viscosity when irradiated by the UV light [ 5 ]. A study by Cho et al demonstrated the possibility of implementing damper and flow valves based on the principle of viscosity changes of PR fluids [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…PR fluids are characterized by changes in their properties such as color and viscosity when irradiated by the UV light [ 5 ]. A study by Cho et al demonstrated the possibility of implementing damper and flow valves based on the principle of viscosity changes of PR fluids [ 5 , 6 ]. Meanwhile, Jin et al experimented with PR fluids to verify the dual-response characteristic evoked by UV light and temperature [ 7 ].…”
Section: Introductionmentioning
confidence: 99%